Sphingosine-1-phosphate in the plasma compartment regulates basal and inflammation-induced vascular leak in mice - Camerer, Eric (American Society for Clinical Investigation, 2009)
Maintenance of vascular integrity is critical for homeostasis, and temporally and spatially regulated vascular leak is a central feature of inflammation. Sphingosine-1-phosphate (S1P) can regulate endothelial barrier function, but the sources of the S1P that provide this activity in vivo and its importance in modulating different inflammatory responses are unknown. We report here that mutant mice engineered to selectively lack S1P in plasma displayed increased vascular leak and impaired survival after anaphylaxis, administration of platelet-activating factor (PAF) or histamine, and exposure to related inflammatory challenges. Increased leak was associated with increased interendothelial cell gaps in venules and was reversed by transfusion with wild-type erythrocytes (which restored plasma S1P levels) and by acute treatment with an agonist for the S1P receptor 1 (S1pr1). S1pr1 agonist did not protect wild-type mice from PAF-induced leak, consistent with plasma S1P levels being sufficient for S1pr1 activation in wild-type mice. However, an agonist for another endothelial cell G(i)-coupled receptor, Par2, did protect wild-type mice from PAF-induced vascular leak, and systemic treatment with pertussis toxin prevented rescue by Par2 agonist and sensitized wild-type mice to leak-inducing stimuli in a manner that resembled the loss of plasma S1P. Our results suggest that the blood communicates with blood vessels via plasma S1P to maintain vascular integrity and regulate vascular leak. This pathway prevents lethal responses to leak-inducing mediators in mouse models.